How TikTok Enhances Speaking Skills in 11th Graders at SMAN 14 Bandar Lampung - Rini , Yulan Puspita; Kholid, M. Fikri Nugraha; Taliban, Khojin (Lexeme : Journal of Linguistics and Applied Linguistics, 2024)
This study aims to determine whether TikTok significantly influences the speaking skills of eleventh-grade students in the second semester at SMA Negeri 14 Bandar Lampung during the academic year 2023-2024. TikTok is an application not only for entertainment but also as a learning medium, especially for speaking skills. This study uses a quantitative approach with a pre-experimental design, specifically a one-group pretest and posttest design. The population in this research consisted of 274 students across 8 classes. The sample size was 35 students from the second semester of the eleventh grade at SMA Negeri 14 Bandar Lampung. The material used in this research focused on asking and giving opinions. Data were obtained before and after treatment. The students were given a pre-test to make a conversation involving asking and giving opinions. Then, the students received treatment using TikTok videos as a learning medium. Finally, the students took a post-test with the same material but on a different topic. The data analyzed included the average scores from the researcher as the first observer and the teacher as the second observer. The data were analyzed using a paired sample t-test through SPSS 16. The results obtained from SPSS 16 showed a significance value (Sig.) of 0.000 with α = 0.05, indicating that Ha was accepted because Sig. < α. Therefore, the study shows that TikTok significantly influences the speaking skills of eleventh-grade students at SMA Negeri 14 Bandar Lampung in the academic year 2023-2024.